Soviet Climate Change Science Domestic Debates, International Collaboration and Future Climates - Oldfield, Jonathan D.; Jankovic, Vladimir; Doose, Katja; Kruglikova, Nina; Shaw, Denis J.B.; Lajus, Julia (London Taylor & Francis; Routledge, 2025)
Chapter 1 Soviet science and the challenge of climate change Chapter 2 Institutional underpinnings of climate science in the Soviet Union Chapter 3 Soviet scientific debates concerning climate change Chapter 4 Cold War climate science: collaboration and competition, 1945-1991 Chapter 5 Greenhouse glasnost Chapter 6 Soviet climate science, its legacies and climate politics Chapter 7 Conclusion
E-Book / Zugriff nur im Lesesaal
Keywords: Klimawandel; Klimaforschung; Umweltforschung; Sowjetunion